Factors affecting the interest rate policy of commercial banks (Journal of Economic Research & Business Administration, 2018)
The subject of the flock is conditioned by the need to consider the influence of internal and externalfactors on the interest rates of banks. The purpose of the study is a comprehensive, reliable study of themain factors influencing the formation of interest rates on the basis of methods of cognition developedin science, as well as obtaining and implementing recommendations of results and conclusions. Thechoice of the direction of scientific research is related to the need to compile an idea of the features andmethods of forming the interest policy of the bank. The research used the method of analysis, synthesis,observation and collection of factual information that allowed studying economic phenomena both inparts (analysis) and in general (synthesis).The article examines the factors influencing the interest rates of commercial banks, which depend primarilyon the macroeconomic situation in the country. The National Bank of the Republic of Kazakhstan acting asthe main regulator also affects the interest rate policy of banks through the establishment of a base rate. The interest rate also depends on the size of the loan. Also, the value of the interest rate depends on the security ofthe loan. As a market value, the interest rate depends on the demand and supply of money, the developmentof the money market, the sources of free money, borrowed funds (their creditworthiness, reliability in repaymentof borrowed funds), and other factors. The market rate of loan interest is determined by the interactionof supply and demand in the credit market. The study of the influence of all the above factors on the interestrate of commercial banks forms the basis of this article. The results summed up in the work are of practical importance,and the conducted research has revealed the main factors influencing the interest policy of banks.